Mitos e monumentos: a construção de identidades paulistanas (1920-1955) - Moreira, Marcos Rogério da Silva (2017)
This dissertation aims to investigate the construction of social identities present in the city of São Paulo and its intrinsic connection with the formation of materialized and guided by monuments erected in places arbitrarily chosen as places of memory. Through the study and analysis of historical monuments present in the city of São Paulo, namely the Monumento às Bandeiras and the Monumento à Mãe Preta, which were proposed as landmarks and places of memory for the establishment of paulistanas identities, this research aims to understand social interactions and life experiences of its founders and their relations the political and social events in the historical context in which they operate